2017
DOI: 10.1007/s10815-016-0865-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular inflammatory cytokines but not steroid hormone concentrations are increased in naturally matured follicles of women with proven endometriosis

Abstract: Purpose The aim of this study was to assess whether the intrafollicular cytokine profile in naturally developed follicles is different in women with endometriosis, possibly explaining the lower reproductive outcome in endometriosis patients. Methods A matched case-control study was conducted at a university-based infertility and endometriosis centre. The study population included 17 patients with laparoscopically and histologically confirmed endometriosis (rAFS stages II-IV), each undergoing one natural cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…The results of the study by Pellicer et al were confirmed in the study of Wu et al (2017) in natural cycle IVF in women with moderate-to-severe endometriosis. On the other hand, Opøien et al (2013) found no difference in cytokine levels (IL1B, IL6, IL8, IL10, IL12 and TNFa) in the leading follicle adjacent to endometriomas.…”
Section: Cytokines In Ff Of Patients With Endometriosismentioning
confidence: 71%
See 1 more Smart Citation
“…The results of the study by Pellicer et al were confirmed in the study of Wu et al (2017) in natural cycle IVF in women with moderate-to-severe endometriosis. On the other hand, Opøien et al (2013) found no difference in cytokine levels (IL1B, IL6, IL8, IL10, IL12 and TNFa) in the leading follicle adjacent to endometriomas.…”
Section: Cytokines In Ff Of Patients With Endometriosismentioning
confidence: 71%
“…Possibly, the higher levels of FF cytokines are produced by the granulosa cells or the FF immune cells which might be more activated in endometriosis. However, the activity of these FF immune cells is yet to be analyzed in endometriosis patients (Wu et al 2017).…”
Section: Cytokines In Ff Of Patients With Endometriosismentioning
confidence: 99%
“…Indeed, follicular fluid is an active microenvironment which has a critical role in oocyte growth and maturation. Differences in the concentration of inflammatory cytokines [31][32][33] and oxidative stress markers [34,35] in follicular fluid have been reported between women with and without endometriosis. Endometriosis could also affect the metabolic processes, thereby altering the microenvironment of the follicle and the oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…В нескольких исследованиях показано, что эндометриоз яичников и других участков тазовой области может отрицательно влиять на стероидогенез гранулезных клеток (ГК) яичников, уменьшая экспрессию ароматазы P450, являющейся ключевым ферментом синтеза эстрогенов, согласно теории двух клеток, и выработку 17β-эстрадиола (E 2 ) [10,23]. Эстрадиол, в свою очередь, имеет решающее значение для развития фолликулов и образования компетентного ооцита, способного достичь стадии МII и оплодотвориться [7].…”
Section: Endometriosis and Oocytes (A Review)unclassified